Cutaneous mantle cell lymphoma: A rare case report - Salwa Bano; Veena Ramaswamy; B N Tejaswini; Chaitra Chandrashekar (Wolters Kluwer Medknow Publications, 2020)
Cutaneous mantle cell lymphoma (MCL) is a very rare entity with very few cases reported till date. We report a case of 69-year-old man with generalized lymphadenopathy who was diagnosed with mitotically active B-cell lymphoma and a year later developed multiple large maculopapular skin rashes which on biopsy showed infiltration of large atypical blast-like cells in the skin and on immunohistochemistry was in favor of MCL-blastoid variant. Skin involvement is rare in MCL, although in some cases, cutaneous manifestations are the first symptom. Skin involvement suggests a disseminated disease and is often associated with blastoid cytological features. Awareness of skin manifestations of MCL is crucial for dermatologists and hematologists for prompt diagnosis and timely treatment. Moreover, it has a dismal prognosis and shows a poor response to standard treatment.